On the Structure of Commutative Rings with ${\bf {p_1}^{k_1}… {p_n}^{k_n} Zero Divisors II (European Journal of Pure and Applied Mathematics, 2010)
In this paper, we determine the structure of nonlocal commutative rings with $p^6$ zero-divisors and characterize the structure of nonlocal commutative rings with $p^7$ zero-divisors. Also, the structure and classification up to isomorphism all commutative rings with ${p_1}^{k_1}… {p_n}^{k_n}$ zero-divisors, where $n$ is a positive integer, ${p_i}^,s$ are distinct prime number and $1≤ k_i≤ 4$, are determined.